Breaking immersion: A theoretical framework of alienated play to facilitate critical reflection on interactive media - Aeschbach, Lena Fanya; Opwis, Klaus; Brühlmann, Florian (Frontiers in Virtual Reality, 2022)
There is a growing interest in understanding how to best represent complexity using IDNs. We conceptualize this as the aim to make players of such IDNs reflect critically on the complexity being represented. We argue that current understandings of player experience do not lend themselves to this aim. Research on interactive media has assumed immersion to be a universal positive for the player experience. However, in this article we argue that immersion into the Magic Circle of an IDN could be antagonistic to a critical experience. This is because immersion persuades players into suspending their disbelief, rather than facilitating critical reflection. Instead we propose, on the basis of the Epic Theater, an alternative form of play called alienated play. Meaning, a form of play in which the player is playing, while also observing themselves play. This form of play should allow for players to benefit from the enjoyable nature of play, while simultaneously remaining at a critical distance. To illustrate our theory we design two models, one for immersed play and one for alienated play. Furthermore, we present examples of the design for alienation in commercial video games, as well as hypotheses to test out theory in future research. Therefore, this work contributes an initial theoretical and practical informed form of play, specifically designed to facilitate critical reflection on IDNs representing complexity.